The Relationship between Family Support and Anxiety Level in Preoperative Elderly with Spinal Anesthesia Action at AR Bunda Prabumulih Hospital, South Sumatra: English - Rahmatsyah Zulda, Alvian; Nova Handayani, Rahmaya; Heri Susanti, Indri (Global Indonesia Health Care (GOICARE), 2023)
Purpose: This study aims to determine the relationship between family support and anxiety levels in elderly people pre-operatively with spinal anesthesia at Ar Bunda Prabumulih Hospital, South Sumatra. Methods: This research uses a quantitative descriptive method with a cross sectional approach. The sample in this study was elderly patients with spinal anesthesia techniques who met the criteria. The sampling technique used was consecutive sampling using the Arikunto formula to produce 34 respondents. And data analysis using univariate and bivariate analysis. Findings: The research results showed that the majority of respondents had moderate family support, 23 respondents (67.6%), the majority of respondents had moderate anxiety levels, 16 respondents (47%), the results of statistical tests using Spearman's Rank obtained a p-value of 0.032, so the p-value < α (0 .05). Conclusions: This shows that H0 is rejected and Ha is accepted, meaning that there is a relationship between the respondent's pre-operative anxiety level and family support during treatment in the operating room at AR Bunda Prabumulih Hospital. It is hoped that future researchers will be able to develop related research to look for variables and factors that may be related to the incidence of anxiety levels after spinal anesthesia in surgical patients.